A survey of impression materials and techniques in fixed partial dentures among general dental practitioners and prosthodontists in India - Dibyatanu Majumder; Saha, Sarmishtha; Sengupta, Parama (Asian Journal of Medical Sciences, 2022)
Background: Replacement of missing tooth plays an important role in patient’s comfort and self-esteem. Aims and Objectives: The aims of this study were to investigate the most commonly used impression materials and techniques practiced for crowns and bridgework by prosthodontists and general dental practitioners compared to the theoretical methods suggested in the literature and to determine the clinical factors that might influence the decision-making process for the selection of impression materials and techniques. Materials and Methods: Pre-tested and pre-validated structured and closed-ended anonymous questionnaire was shared with general dental practitioners and prosthodontists. Results: Most of the prosthodontists use diagnostic impression compared to general dental practitioners (P<0.01). Full-arch tray was used by general dental practitioners significantly more frequently compared to prosthodontists (P<0.01) for single anterior, single posterior, anterior, and posterior bridge preparations. Alginate hydrocolloid was used by general dental practitioners significantly more than prosthodontists (P<0.05); however, addition silicone and condensation silicone were used by prosthodontists significantly more than general dental practitioners (P<0.05). For the impression technique followed in case of using elastomeric impression materials, the prosthodontists used the two-step putty reline technique with spacer more commonly, while general dental practitioners used the multiple mix technique (P<0.01). For the use of provisional restoration for single tooth crowns and for all the bridges, prosthodontists used provisional restoration in significantly higher proportion as compared to general dental practitioners (P<0.01). Conclusion: According to our study compared to general dental practitioners, practices of the prosthodontists regarding use of fixed partial denture is more in line with the current global trend.